“NEW UZBEKISTAN NEW NEIGHBORHOOD” - Kadirova Dildora Sabirdjanovna (Western European Studies, 2024)
The article examines the topical problems of reforming the system of makhallas in Uzbekistan, the peculiarities of organizing the activities of multinational, religious communities and democratic factors in the years of independence, It is narrated on the content of the Mahallabay Working System
Keywords: Ministry of Mahalla and Family Support; Appeal to Oliy Majlis; religious communities